Encouraging the Participation of Village Human Resources in Village Development Pematang Serai, Langkat (Mendorong Partisipasi Sumber Daya Manusia Desa dalam Pembangunan Desa Pematang Serai, Langkat) - Andika, Rindi; Rizky, M. Chaerul; Ritonga, Husni Muharram; Nurhaliza, Ika (UKInstitute, 2025)
The service activity with the theme Encouraging the Participation of Village Human Resources in the Development of Pematang Serai Village, Langkat aims to increase the capacity of human resources (HR) at the village level as the key to sustainable development. Through a series of trainings, workshops, and discussions, village communities are provided with relevant practical knowledge and skills, as well as an understanding of the importance of their active role in the development process. This activity succeeded in creating a collective awareness of shared responsibility in community development, as well as encouraging collaboration between various stakeholders. In addition, this activity strengthens the social network among the participants, which is expected to continue to support future development initiatives. The results of this activity show an increase in skills, active participation, and potential for local economic development, which overall contributes to the progress of Pematang Serai Village. Thus, this activity is a strategic step in realizing an independent, competitive, and sustainable village.Abstrak: Kegiatan pengabdian dengan tema Mendorong Partisipasi SDM Desa dalam Pembangunan Desa Pematang Serai, Langkat ini bertujuan untuk meningkatkan kapasitas sumber daya manusia (SDM) di tingkat desa sebagai kunci pembangunan berkelanjutan. Melalui serangkaian pelatihan, lokakarya, dan diskusi, masyarakat desa dibekali dengan pengetahuan dan keterampilan praktis yang relevan, serta pemahaman tentang pentingnya peran aktif mereka dalam proses pembangunan. Kegiatan ini berhasil menciptakan kesadaran kolektif akan tanggung jawab bersama dalam pembangunan masyarakat, sekaligus mendorong kolaborasi antar berbagai pemangku kepentingan. Selain itu, kegiatan ini memperkuat jaringan sosial di antara para peserta, yang diharapkan dapat terus mendukung inisiatif pembangunan di masa mendatang. Hasil kegiatan ini menunjukkan adanya peningkatan keterampilan, partisipasi aktif, dan potensi pengembangan ekonomi lokal, yang secara keseluruhan berkontribusi terhadap kemajuan Desa Pematang Serai. Dengan demikian, kegiatan ini merupakan langkah strategis dalam mewujudkan desa yang mandiri, berdaya saing, dan berkelanjutan.